Building sustainability strategy in business. Issue 6 (16th November 2015) - Teh, David; Corbitt, Brian
Abstract : Purpose: – The purpose of this paper is to explore environmental sustainability (eco-sustainability) policy and strategy adoption and implementation in Australian companies. Specifically, it assesses what influences the extent of organizational eco-sustainability strategy implementation. Design/methodology/approach: – This research used semi-structured interviews with senior executive from a list of the Australian Securities Exchange (ASX) 200 companies in banking, materials, real estate and transportation industry groups. A purposive sampling method was used to select the most appropriate participants. The "elite" interviewing method was adopted with persons who are recognized as the expert in the topic under investigation. Finally, an interpretative approach to data analysis was used. Findings: – The paper shows the importance of eco-sustainability strategy alignment with the overall business strategy. Similarly, organizational structure and systems are recognized to be equally important. The senior executives also agreed that shared values, passionate skilled and experienced staff, the Board and senior management, as well as governance, are critical in ensuring a successful adoption and implementation of organizational eco-sustainability policy and strategy. Practical implications: – This research provides some understanding of how organizations implement their eco-sustainability policy and strategy and what influences the extent of their eco-sustainability strategy implementation, and answers to why each dimension is important for a particular organization was gained through interviews with the senior executives. This paper also facilitates a better understanding of the relative importance placed on each dimension as a factor influencing eco-sustainability adoption and implementation. Originality/value: – Drawing on theories from various disciplines and the McKinsey Seven S's framework, this paper strengthens the foundation for industry practitioners to understand what influences the success of the eco-sustainability strategy adoption and implementation.